Stress state analysis in belt drive systems and determination of their optimal operating modes (Международный научный журнал «Инженер», 2026)
This scientific article analyzes the forces that occur in belt drives and their impact factors. Belt tension, wheeldiameters, and rotational speed are considered as input factors in the study. The moment transmitted through thetransmission and the dynamic loads acting on the belt are studied as output factors. The relationship betweenthese factors is expressed using mathematical modeling and optimal working conditions are determined. Themain purpose of the study is to determine the optimal parameters for improving the efficiency of belt drives andensuring their reliability.